Measuring Optimal Reading Experiences: The Reading Flow Short Scale - Thissen, Birte A. K.; Menninghaus, Winfried; Schlotz, Wolff (Frontiers in Psychology, 2018)
In transferring the concept of flow to the context of fiction reading a new approach to understanding the evolvement of reading pleasure is provided. This study presents the Reading Flow Short Scale (RFSS), the first reading-specific flow measurement tool. The RFSS was applied to 229 readers via online survey after 20 minutes of reading in self-selected novels. In a systematic analysis of psychometric properties, the RFSS’ factorial structure, reliability, and associations with theoretically-related constructs were examined. As expected, the RFSS showed a two-factor structure, positive correlations with variables related to reading pleasure and flow, and an inverted U-shaped association with perceived fit between reader skills and text challenge. Comparisons of confirmatory factor analysis model confirmed that RFSS items loaded on different latent variables than items assessing other narrative engagement concepts, namely presence, identification, suspense, and cognitive mastery, and hence distinctly capture flow states in fiction reading. In sum, our findings indicate that the RFSS is a useful instrument for assessing flow states in fiction reading, thereby enriching the portfolio of measurement instruments in reading research.